2019
DOI: 10.1002/we.2358
|View full text |Cite
|
Sign up to set email alerts
|

Performance and wake of a Savonius vertical‐axis wind turbine under different incoming conditions

Abstract: In this study, the performance, drag, and horizontal midplane wake characteristics of a vertical‐axis Savonius wind turbine are investigated experimentally. The turbine is drag driven and has a helical configuration, with the top rotated 180° relative to the bottom. Both performance and wake measurements were conducted in four different inflow conditions, using Reynolds numbers of ReD≈1.6×105 and ReD≈2.7×105 and turbulence intensities of 0.6% and 5.7%. The efficiency of the turbine was found to be highly depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…The control of the tip speed ratio was fixed between different measurement positions leading to slight variations between 0.62 and 0.78. The values are in line with expected values for Savonius-type turbines (Akwa et al, 2012;Aliferis et al, 2019).…”
Section: Wind Turbine Performancesupporting
confidence: 88%
“…The control of the tip speed ratio was fixed between different measurement positions leading to slight variations between 0.62 and 0.78. The values are in line with expected values for Savonius-type turbines (Akwa et al, 2012;Aliferis et al, 2019).…”
Section: Wind Turbine Performancesupporting
confidence: 88%
“…Aliferis et al. (2019) studied the 2-D planar wake structure of a Savonius-type VAWT with helical blades using a Cobra probe on a traverse. Lastly, Ouro et al.…”
Section: Introductionmentioning
confidence: 99%
“…Schuerich & Brown (2011) used a vorticity-transport model for this purpose, and Cheng et al (2017) approached the problem using unsteady RANS, 2-D LES and wind-tunnel experiments. Aliferis et al (2019) studied the 2-D planar wake structure of a Savonius-type VAWT with helical blades using a Cobra probe on a traverse. Lastly, Ouro et al (2019) analysed turbulence quantities in the wake of a helical-bladed VAWT in a water channel using pointwise velocity measurements from an anemometer on a traverse.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, SAWINT is the only studied turbine with a small end plate area (its geometric design is made for ice breaking in extreme cold conditions), causing fluid leakage from the concave side of the blade to the external flow, dramatically affecting its aerodynamic performance [15]. The wake is deflected in the same direction where the blades move opposite to the flow, as it was in [12].…”
Section: Discussionmentioning
confidence: 99%
“…Experimentally, Damak et al [10] and Saha et al [11] further revealed the potential that the twisted bladed rotor possesses as compared to the conventional Savonius turbine under specific conditions. The wake from the turbine with helical configuration, experimentally investigated by Aliferis et al [12], was found to be asymmetrical and deflected to the side where the blade moves in the opposite direction to the incoming wind. Kumar and Saini [13] carried out a numerical analysis aiming to optimize the blade twist angle of a Savonius hydrokinetic turbine.…”
Section: Introductionmentioning
confidence: 99%